Test results of new breeding potato hybrids in the conditions of the Volga-Vyatka region - O. N. Bashlakova (Аграрная наука Евро-Северо-Востока, 2024)
In the period from 2016 to 2022 in the conditions of the Kirov region, an assessment of hybrid potato combinations was carried out according to the most important traits - high productivity and yield, marketable and consumer qualities of tubers. New potato hybrids bred by the Falenki Breeding Station – branch of the FARC North-East were used as the objects of the research: 6-17 (‘Gornyak’ x ‘Manifest’); 15-17 (428-05 x ‘Manifest’); 33-17 (132-07 x ‘Manifest’); 72-17 (‘Gornyak’×‘Irbitsky’); 78-17 (‘Udacha’ x 428-05); 120-17 (‘Utyonok’×‘Reggi’); 25-16 (‘Kupalinka’ x 428-05). They were noted as the most promising ones according to the results of the research of 2016-2022. The medium-early ‘Nevsky’ cultivar approved for use in the Kirov region was used as a standard. According to the methodological guidelines of the potato breeding process, phenological observations, productivity assessment (on day 65), total and commercial yields were carried out in the nursery, and the chemical composition of tubers was determined. As a result, on average, over three years of testing for a complex of economically valuable traits, a promising breeding number 33-17 was identified – a significant excess of the total yield (29.9 t/ha) over the standard ‘Nevsky‘ cultivar was 14.6 t/ha. The tubers are oval with a red, slightly reticulated skin, the eyes are small, unpainted, the flesh is white. In addition, when evaluating the productive capabilities of potato hybrids, the coefficient of adaptability of breeding number 33-17 was 1.40, which makes it possible to recommend it for cultivation in this region in order to obtain stable yields.